DESIGN AND IMPLEMENTING A HEAT PIPE EXPPERIMANTAL SYSTEM FOR RESIDENTIAL HEATING (Journal of Engineering, 2007)
The design and construction of an instrumented heat pipe H.P for domestic heating that uses water as a working fluid was undertaken to investigate experimentally the performance of the H.P under various operating conditions of: Power levels, water inventories and angle of inclinations. A theoretical model to predict the temperature of the condenser surface (the temperature at which heat is rejected) and system pressure at steady state conditions was developed and used to compare these parameters with the experimental findings. The model utilizes the total heat supplied to the evaporator to predict system pressure and condenser temperature. The theoretical model is suitable for vertical H.P (i.e.  =0) and its predictions of condenser surface temperature is within 16% and of system pressure is within 21%. An acceptable H.P design may have a condenser heat flux of 1.16 k W/m2 with a corresponding system pressure of 1500 kPa.